Fungal Pathogens of Peach Palm Leaf Spot in Thailand and Their Fungicide Sensitivity - Prisana Wonglom; Nakarin Suwannarach; Jaturong Kumla; Anurag Sunpapao (Journal of Fungi)
Peach palm (Bactris gasipaes Kunth) is a long-lived tropical palm valued for its edible, nutritious fruits. The cultivation area of peach palm, which was introduced to Thailand for fruit production, has been steadily expanding. Small brown spots that expanded into irregular lesions with dark margins were first observed on B. gasipaes seedlings in commercial nurseries in Phetchaburi Province, southern Thailand. To identify the causal pathogens, ten fungal isolates were obtained from symptomatic leaves and subjected to pathogenicity tests, confirming their ability to cause the disease. Morphological and molecular analyses identified five isolates as Colletotrichum fructicola (BGC02.2, BGC03) and C. theobromicola (BGC01, BGC02.1, BGC04) and five isolates as Fusarium pernambucanum (BGF01, BGF02, BGF03, BGF04.1, BGF04.2). Phylogenetic analysis was based on act, cal, gapdh, ITS, and tub2 regions for Colletotrichum spp. and cal, rpb2, and tef1-α for Fusarium spp. In vitro fungicide assays revealed that C. fructicola and C. theobromicola were the most sensitive to carbendazim, mancozeb, and prochloraz, while F. pernambucanum was effectively inhibited by mancozeb and prochloraz. This study represents the first report of C. fructicola, C. theobromicola, and F. pernambucanum causing leaf spot disease on B. gasipaes in Thailand, providing essential insights for disease management strategies in the region.